STUDI LITERATUR: DETERMINAN CAKUPAN IMUNISASI DASAR LENGKAP DI PROVINSI ACEH - Hengki Frengki Manullang; Syafrina Ulfah; Fithri Handayani Lubis (Jurnal Penelitian Kesmasy, 2026)
Immunization is a highly cost-effective public health intervention that plays a crucial role in boosting individual immunity and building herd immunity. Through immunization, the incidence of illness, disability, and death caused by vaccine-preventable diseases can be reduced. However, the coverage of complete basic immunization in Indonesia remains relatively low. According to the 2024 Indonesia Nutrition Status Survey (SSGI), complete basic immunization coverage among children aged 12–23 months reached only 56.1%, with Aceh Province having the lowest coverage at 5.4%. This literature review aims to explore the determinants of complete basic immunization coverage in Aceh Province through a search of the Google Scholar database. A total of 17 selected articles were analyzed in this study. The findings indicate that the determinants of immunization coverage include maternal individual factors (knowledge, education, attitudes, and occupation), family support, health service factors (the role of health workers and access to services), sociocultural factors (community perceptions and beliefs), as well as health policy and system factors, such as financial support through health operational assistance (BOK). Given the complexity of the influencing factors, increasing the coverage of complete basic immunization in Aceh requires a comprehensive, integrated, and sustainable approach involving various stakeholders, including health workers, families, community leaders, and the government.